What’s in your hands? A systematic review of dietary assessment methods and estimation of food sizes in a Primary Care Clinic (2018)
Introduction: Many patients with non-communicable diseases such as obesity are attended to in Family Practice Clinics where quick dietary assessment along with estimation of food sizes as part of lifestyle modification and appropriate intervention could be offered. We performed a systematic review to determine the dietary assessment methods with the best evidence that can be employed in a Family Practice Clinic. Methods: Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines were used to conduct a systematic review of PubMed, Google, and Google Scholar databases from 1992 to 2017. Results: We found 730 original research articles, case–control studies, review articles, proceedings, transactions, and textbooks. Thirty-seven articles were selected out of which two were secondary data, 12 were review articles, 10 were descriptive surveys, and one was a prospective cohort study. There were two randomized controlled trials, two mixed study designs, one working paper, and seven guides. Food portion size estimation using household objects and the hand guide, then the food pyramid guide along with the food-sized plate intervention was documented. Conclusion: In view of the busy nature of Family Practice Clinics in several countries, in performing dietary assessment, food portions can be estimated using household measures and the hand portion guide. The pyramid guide and the portion-sized plate can then be used for intervention.